Báo cáo tổng kết hoạt động của Nhóm nữ đại biểu Quốc hội Việt Nam trong nhiệm kỳ Quốc hội khóa XIV (Số: 52/BC-NNĐBQH) - Nhóm nữ đại biểu Quốc hội Việt Nam (2021)
Toàn văn Báo cáo tổng kết hoạt động của Nhóm nữ đại biểu Quốc hội Việt Nam trong nhiệm kỳ Quốc hội khóa XIV (Số: 52/BC-NNĐBQH)